Radiotherapy as a method of palliative treatment of bone metastases - Milecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2002)
Bone system is one of the frequent sites of distant metastases of cancer. Bone metastases may cause pain and pathologic fractures, or even a cord compression syndrome with severe neurologic symptoms. Radiotherapy play in such case an important role in treatment apart surgery, chemotherapy, hormonal therapy, and bisphosphonathes. Treatment of bone metastases constitutes a significant proportion of the work load of radiotherapy departments, approximately 40%. Typical indications for radiotherapy are pain, pathological bone fracture, and prophylactic irradiation of bone metastases that could cause in spinal cord compression or fracture. The principle rule of management of patients with bone metastases should be the simplicity of treatment no additional side effects in relation to expected short life of patients. Thus, single high-dose fraction plays an important role in irradiation of bone metastases. Currently the optimal schedule of fractionation and total dose are unknown, althouth probably the lowest optimal dose is 8 Gy. Such conclusion is based on results from few randomized trials which compared the treatment results of single fractionation of 8 Gy with other schedules as 6 x 4 Gy or 5 x 4 Gy. Lower single-dose of 4 Gy may play the some role in retreatment since produces overall response rate of 40%. On the other hand, the high single-dose of 15-18 Gy does not give any advantage over moderate hypofractionation single fraction dose (8 Gy). In case of multiple bone metastases half-body irradiation (HBI) with application of single dose of 8-10 Gy or in fractionation schedule 5 x 3 Gy can achieve complete pain relief in over 20% of patients and decrease markedly in the remaining cases (70%). This mode of irradiation is effective and safe with only modest side effects. It may play an important role in management of patients with prostate cancer and multiplex myeloma. Some controversies are concerned with retreatment of previously irradiated bone metastases in case of pain recurrence. In such cases particular attention should be paid for late side effects of treatment. The mechanism by which radiotherapy achieves analgesia is not understood and probably is a mixed response both due to tumor shrinkage and inhibition of pain mediators (prostaglandins, neurogenic peptides). It is worthy to add that bisphosphonates may play an substantial role in decreasing the pain, hypercalcemia, and other complications connected with bone metastases. Thus bisphosphonathes should be a part of treatment of patients with bone metastases.